(untitled) (Modern education and development, 2025)
This article explores the history of the Timurid Empire, a powerful and influential dynasty that flourished in Central Asia from the 14th to the 16th centuries. It examines the empire’s foundation by Timur (Tamerlane), its territorial expansion, political structures, and its significant contributions to art, science, and literature. The article also discusses the empire’s decline and its lasting impact on the regions it governed. It emphasizes the Timurid renaissance, a golden age of cultural and intellectual achievement, and provides an overview of the empire’s enduring historical importance.